Flavonoid-Rich Extract of Paeonia lactiflora Petals Alleviate d-Galactose-Induced Oxidative Stress and Restore Gut Microbiota in ICR Mice - Lei Liu; Yingdan Yuan; Jun Tao (MDPI AG, 2021)
This study was aimed to investigate the antioxidant effect of Paeonia lactiflora Pall. petal flavonoids extract (PPF) on d-galactose (d-gal)-induced ICR mice. In this study, sixty male ICR mice were randomly divided into six groups during an 8 weeks experimental period, including normal control (NC) group, d-gal group, epigallocatechin gallate (EGCG) group, low, medium, and high dose PPF groups (10, 20 and 40 mg/kg/day). The results showed that intragastric administration with PPF significantly reverses the atrophy of the visceral organs of oxidative damage mice in a dose-dependent relationship. PPF indicated the antioxidant capacity to decrease the malondialdehyde (MDA) level and improve the activity of superoxide dismutase (SOD), catalase (CAT) as well as glutathione peroxidase (GSH-Px). In addition, PPF treatment reversed gut microbiota dysbiosis by increasing the relative abundance of Lactobacillaceae. Spearman correlation analysis showed that the body's oxidative stress markers were directly related to changes in gut microbiota. These findings reveal firstly that PPF could alleviate d-Gal-induced oxidative stress and modulate gut microbiota balance.